An Evaluation Of Marine Shrimp Resource Policy In Indonesia:The Case Of The Trawler Ban - Tridoyo Kusumastanto (Jurnal Ilmu-Ilmu Perairan dan Perikanan Indonesia, 1995)
As the largest archipelagic nation in the world, Indonesia has a huge marine resources that is contained in 3.1 million kilometer square (km) territorial waters and 2.5 milliom km2 of 200-mile Exclusive Economic Zone (EEZ).Indonesia also has the world's longest coastline (81,000 km) lying in 13,667 islands straddling the equator. Those resources are veryimportant for the development of marine capture and mariculture fisheries(see Appendix 1).In more recent years, marine resource has become increasi ngly significant as a source of national wealth.The exploitation of petroleum resources in Indonesia waters, combined with land-based operati ons, has made a significant contribution to the Indonesian and has permitted large investments in national and rural development.The fisheries sector also have contributed to Indonesia's export earning, totalling US$ 475.5 million in 1987, shrimp accounted for US$ 352.4 (74.1 %), tuna (including skipjack) US$ 30.9 million (6.5%) and others US$ 92.2 million (19.4%) (DGF, 1990).Within the fisheries, the marine c.1pture sector continues to dominate, accounting for 76% of tonnage (2.029 million ton), and inland water fisheries 24 % of tonnage (.641 million ton) in 1987 .Aquaculture is expanding rapidly especially after "Trawler Ban" in 1980 ) which decreased 21.6 % shrimp exported in 1981. Brackish water aquaculture contributed 28.5 % of shrimp production in 1987 which increased almost I 7.4% per yearsince 1983 but marine shrimp production still constitute the majority of shrimp supplies both domestic consumption and export (64%) .